MENGATASI RINTANGAN STRUKTURAL: AKAR KONSEPTUAL DAN PRAKTIK EMPIRIK GOVERNANCE ANTIKEMISKINAN (Inisiatif Antikemiskinan Organisasi non-Pemerintah (NGO) dan Ormas Islam (MBO) di Jawa Tengah, Jawa Timur, dan Nusa Tenggara Barat) - Sobari, Wawan (Jurnal Interaktif, 2010)
Conventional approach views that the root of poverty is inherently cultural factors. Indeed, structural factors outside the poor are the real impediments. This paper discusses three questions focusing on governance of antipoverty. It covers extension of the actors, policy change, and transformation of the poor. This paper found on the result of study applying qualitative approach to build understanding on initiatives ofÂ  non-state actors (NGO and MBO) in participating to eradicate poverty. In gathering data, researcher undertakes semi-structured interview. Also, this study deploys documents and secondary data collection to counter the interview pitfalls.This paper demonstrates three main findings. Governance of antipoverty has allowed non-state actors to extend the involvement of more various actors and to create a new space in the arena of pro-poor policy making. Also, initiatives of non-state actors have endorsed inclusive pro-poor policy, particularly the alteration of budget allocation. Finally, the exercise of participatory tools and techniques have transformed behavior and capacity of the poor as well as networking among the poor, NGO, MBO, and local government. Nonetheless, interest and ideological differences between NGO and MBO can hamper collaboration among them. Key words: governance, policy networks, poverty alleviation, non-government actors